A Competitive Study Of Car Sales In Business And E-Business - Tang, Mei Yu (2005)
The purpose of this study is to describe CRM and the realization of CRM in companies by using a CRM system. The research in this study can be considered as both exploratory and descriptive, but mainly explorative.